Hydrotechnical concrete with local aggregates and them using for monolithic structures - Vigantas Antanas Žiogas; Svajūnas Juočiūnas; Giedrius Žiogas (Engineering Structures and Technologies, 2009)
The article discusses the technological peculiarities of construction monolithic hydrotechnical concrete structures, use of local aggregates for producing special concretes, methods of determining water impermeability of concretes as well as the evaluation of the methods mentioned above. The article presents the requirements for the granulometric composition of aggregate mixes for the production of flowing concrete mixes used for the construction of monolithic hydrotechnical structures. The possibilities and expediency of using local crushed gravel with increased amounts of weak particles for hydrotechnical structures are discussed. The mass loss of weak particles is slight compared with the whole mass of aggregates, and the total mass loss of crushed gravel it occurs due to micro-cracks present in particles. The frost resistance mark of crushed gravel and its suitability for hydrotechnical concretes should be determined by evaluating the amount of weak particles and their frost resistance. The article discusses concrete impermeability data received by means of two methods (according to LSTST 1974:2005 and LSTST EN 12390–8 requirements). Theoretical water penetration depths have been calculated. Determination of water impermeability according to LSTST 1974:2005 is recommended for C25/30 and lower compressive strength class concretes with W≤8. The LSTST EN 12390–8 water impermeability determina-tion method is recommended for C25/30 and higher compressive strength class concretes whose water impermea-bility mark is W≥8. For the construction of certain hydrotechnical structures water impermeable concretes whose water penetration depth should not exceed 20mm are recommended for use instead of the W6 and W8 concretes. Technological peculiarities and potential technological-organizational solutions for high walls of a water treatment plant have been discussed. The analysis of potential concreting methods of the reservoir’s high walls has been made as well as that of the key parameters of the continuous concreting process and their interaction. Dependences for the estimation of continuous concreting volumes and permissible concreted segment lengths have been proposed by evaluating the beginning of the intensive formation structure of concrete, number of layers in the height of the concreted wall and concreting intensity.